(untitled) (REMUNOM, 2025)
Fencing, like tennis, is a one-sided sport and is played with a mediating instrument (foil, saber, épée; racket in tennis), and this equipment have different weights. The foil weighs 0.5 kg; the saber should weigh less than 0.77 kg, usually 0.5 kg; and the épée weighs 0.77 kg; The tennis racket, on the other hand, weighs about 0.30 kg. This involves a one-sided use of the body’s muscles. The aim of this study was to evaluate the accuracy of movement and motor behavior of sensorimotor responses corresponding to each motor stimulus. We applied to Physical Education students at the Federal University of Paraná (UFPR), during Fencing classes and we searched the literature on athletes to compare the psychomotor variables. These variables are linked to natural components necessary for an athlete, such as cognition, perception, memorization, attention, and reasoning. Keywords: Postural balance. Tactile stimulus. Fencing. Movement time. Reaction time